Avaliação da qualidade óssea de doença osteometabólica experimental em jacarés-do-pantanal (Caiman yacare) por microtomografia computadorizada (µCT) de alta resolução - Becker, Marciel (2017)
Computerized microtomography is the gold standard examination for the evaluation of the three-dimensional bone structure. This experimental study was developed to evaluate the structure and bone quality of Caiman yacare (Caiman yacare) with metabolic bone disease using high resolution computerized microtomography (μCT). The animals were distributed into four groups: G1 - hyperphosphatemic diet with sunlight deprivation (n = 4), G2 - hyperphosphatemia diet with sunlight exposure (n = 4), G3 - 4) and G4-balanced diet with exposure to sunlight (n = 4). The parameters for the trabecular bone (Trabecular Number, Trabecular Thickness, Trabecular Separation, Bone Pattern Factor, Fractal Dimension, Euler Number, Structural Model Index, Degree of Anisotropy, Eigenvalues 1,2 and 3, and Centroides X , Y and Z) and cortical bone (Number of Closed Pores, Volume of Closed Pores, Surface of Closed Pores, Closed Porosity, Volume of Open Pores, Open Porosity and Total Porosity). The overall results showed that the structure and bone quality of Group G3 and G4 were better than those of Groups G1 and G2, and that the diet factor influenced more than the sun exposure factor. The computerized microtomography allowed to evaluate the quality of the cortical and trabecular bones of the pantanal alligator tibia with osteometabolic disease. The diet and sun exposure factors influenced individually the results of the μCT parameters between the groups, demonstrating the functional and structural complexity. Thus, these parameters can contribute to the interpretation of the functional and mechanical behavior of bone in osteometabolic diseases.